Evaluation of cartographic functional styles for wind energy mapping - Viliuviene, Rita; Bevainis, Linas (Advances in Geodesy and Geoinformation, 2025)
Functioning of maps in different areas of human activity provides the right context for the formation of cartographic functional styles. The community that participates in this map-related activity gains knowledge. When developing a system of cartographic functional styles, it is important to consider how users value cartographic functional styles. The purpose of the research is to evaluate cartographic functional styles based on the results of the target group survey. In order to achieve the goals of the research, the framework of the system of cartographic functional styles has been prepared, consisting of the main components that determine the cartographic functional style. Maps illustrating characteristic features of different styles are included. A questionnaire for the survey was prepared. Stylistic analysis of modern maps, analysis of information sources was carried out during the research. The maps are produced using data from different data sources and GIS software. 4 maps on the current topic of wind energy are the results of this activity. 104 respondents from different fields of activity took part in the survey. The results of the survey show that as many as 85 percents of the respondents basically agree with the statement that maps in general are characterized by a variety of cartographic functional styles. The respondents give high priority to the target audience for which the map is intended in the system of functional styles. Based on the results of the survey, the framework of the system of cartographic functional styles has been specified.